Formal synthesis of tetrahydrolipstatin and tetrahydroesterastin - Tripathi, Divya; Kumar, Pradeep (Tetrahedron-Asymmetry, 2012)
A versatile and efficient approach to (3.5,5R)-methyl 3-(benzyloxy)-5-(methoxymethoxy)hexadecanoate, a key chiral building block and a common polyol fragment of the anti-tumor and anti-obesity agents tetrahydrolipstatin 3 and tetrahydroesterastin 4 using both hydrolytic kinetic resolution (HKR) and proline catalyzed sequential alpha-aminoxylation, followed by HWE-olefination reaction is described. (c) 2012 Elsevier Ltd. All rights reserved.